The Callosobruchus Spp. Controlled Using Soursop Seed Extracts by Several Organic Solvent on Mungbean Storaged Seeds - Chimayatus Solichah; Ami Suryawati (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2017)
The aims of the experiment was to get extract of sour-sop plant part and the kind of organic solvents for decreasing Callosobruchus spp development on mungbean storaged seed. The experiment was conducted at Plant Protection Laboratory, Faculty of Agriculture, UPN “Veteran” Yogyakarta from March to August 2013. It consisted of two factors: the part of sour-sop plant powder (leaves, and seeds) and the kind of organic solvents (Petroleum-eter; Dietil-eter and methanol) and one control: no extract application. It was arranged in Randomized Complete Design with four replications. Data collected was subjected to an analysis of variance followed by DMRT at 5% significance level. The results showed that: 1) The seeds and leaves extract that being solved in organic solvent could supress Callosobruchus spp development better than the control (no extract). 2) The soursop seeds in methanol solvent could supress Callosobruchus development, weight loss of mungbean seed and seed conductivity.Keywords: sour-sop powder, Callosobruchus spp., organic solvent